MODEL PEMBELAJARAN PERMAINAN SEPAKBOLA BAGI SISWA SEKOLAH DASAR I - I Komang Ngurah Wiyasa (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
Game of football is a game that is not foreign to the people of Indonesia. Players ranging from early childhood toadulthood, even old age are still excited to play football. The question is why sports games soccer Indonesia hasnot been able to keep the level of Asia? This is of course necessary to find a solution that ultimately, the future ofIndonesia has a bias player’s file system. It seems that coaching from an early age from the school to its attention.A teacher is expected to improve her professional educators, so that the packing process always focuses on threedomains of learning, namely (1) cognitive, (2) affective, and (3) psychomotor. This paper is essentially to providean overview and understanding that teachers are able to carry out duties in a professional ‘in the field. Teachingprofession is an occupation that emerged from the drive you, so well-loved job as a teacher. This paper examineswritten descriptively with opinions, ideas and comments of the experts on sports learning system in elementaryschool that need attention, particularly on sport football game. Expected in the present study is a process that putsthe students in the learning process, so that teachers act more as facilitators. Teachers should be able to explorethe potential of students with various innovations / model in the learning process that eventually students can findthemselves wide range of skills to play soccer.Keywords: Instructional, Soccer, Elementary School.